Ludic activities to improve speaking skills in 10th basic year students at Jacinto González Huacón high school during school year 2018-2019 - Cercado Martillo, Joice Sabrina (2019)
Today’s current research work needs to be as didactic as possible in order for teaching to be appropriate to students that are learning English. The influence of ludic activities is to improve speaking skills, communication and performance in language learners. Ludic activities give students the opportunity to deal with new learned vocabulary and plain communication. Ludic activities provide the opportunity to self-expanding of thoughts and ideas to students in the language being learned as necessary as possible. The amount of time spent on this practice of the language is what improves gradually with the right set of paces and the realistic terms of the situation………